1995
DOI: 10.1007/bf00029331
|View full text |Cite
|
Sign up to set email alerts
|

Development of root biomass in an Eucalyptus globulus plantation under different water and nutrient regimes

Abstract: The distribution along the soil profile of Eucalyptus globulus root biomass was followed in a plantation in central Portugal at 1, 2 and 6 years after planting, using an excavation technique. The experimental design consisted of a control (C) and 3 treatments: application of solid fertilizers twice a year (F), irrigation without the application of fertilizers (I) and irrigation combined with liquid fertilizers (IL). Below-and above-ground biomass decreased as follows: IL>I>F>C. So, water stress limited growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 18 publications
6
33
0
5
Order By: Relevance
“…Rooting density declined with distance from the drip tube in all genotypes, but rooting density did not decline with distance from tree stems along the drip tubes (x). Drip tubes used for delivery of water and nutrient treatments consistently influence fine-root biomass and density in other woody species including Eucalyptus globulus Labill., l7zuja occidentalis L. and Prunus armeniaca L. (Fabib et al 1995;Pronk et al 2002;Ruiz-Shnchez et al 2005). Use of drip tubes to supply water and fertilizer creates heterogeneous soil conditions.…”
Section: Horizontal Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rooting density declined with distance from the drip tube in all genotypes, but rooting density did not decline with distance from tree stems along the drip tubes (x). Drip tubes used for delivery of water and nutrient treatments consistently influence fine-root biomass and density in other woody species including Eucalyptus globulus Labill., l7zuja occidentalis L. and Prunus armeniaca L. (Fabib et al 1995;Pronk et al 2002;Ruiz-Shnchez et al 2005). Use of drip tubes to supply water and fertilizer creates heterogeneous soil conditions.…”
Section: Horizontal Distributionmentioning
confidence: 99%
“…These relative sample locations were selected to capture spatial heterogeneity in fine-root biomass that was expected to result fiom treatments supplied through the drip tube (cf. Burt and Styles 1994;Fabib et al 1995;Ponder et al 1984;Robinson 1994). In each of the 4 years, five different trees were randomly selected per plot and one of the five relative sample locations was randomly assigned to each.…”
Section: Fine and Medium Root Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatments were daily irrigation from April to October (I); broadcast application of a pelleted fertilizer twice a year (in March and October) (F); and daily irrigation combined with a simultaneous application of liquid fertilizer once a week during the dry season (FI). One and two years after planting, 24 trees (6 trees per treatment) were selected for root measurements from a group of trees randomly harvested for aboveground biomass measurements (Fabião et al, 1995). Six years after planting, only block 2 was available, and a tree with a diameter near the treatment mean was chosen from each plot, for a total of 4 trees (Fabião et al, 1995).…”
Section: Estimation Of Stand Root Biomassmentioning
confidence: 99%
“…The opposite is expected in more productive sites, with more fertile soils, in which the root system would not need to extend as far to absorb the necessary volume of water and nutrients that are vital for metabolic activity. On evaluating the fine root system of Eucalyptus globulus, Fabião et al (1995) found that interference in root growth would be more accentuated in a situation of water stress than for nutrient shortage. Nambiar (1983) reported that other factors may be important in the distribution of forest species fine roots (e.g.…”
Section: Resultsmentioning
confidence: 99%